Recomposing the past representations of early music on stage and screen - Cook, James; Kolassa, Alexander; Whittaker, Adam (Ashgate screen music series, 2018)
Recomposing the Past is a book concerned with the complex but important ways in which we engage with the past in modern times. Contributors examine how media on stage and screen uses music, and in particular early music, to evoke and recompose a distant past. Culture, popular and otherwise, is awash with a stylise - sometimes contradictory - musical history. And yet for all its complexities, these representations of the past through music are integral to how our contemporary and collective imaginations understand history. More importantly, they offer a valuable insight into how we understand our musical present. Such representative strategies, the book argues, cross generic boundaries, and as such it brings together a range of multimedia discussion on the subjects of film (Lord of the Rings, Dangerous Liasions), television (Game of Thrones, The Borgias), videogame (Dragon Warrior, Gauntlet), and opera (Written on Skin, Taverner, English 'dramatick opera'). This collection constitutes a significant, and interdisciplinary, contribution to a growing literature which is unpacking our ongoing creative dialogue with the past. Divided into three complementary sections, grouped not by genre or media but by theme, it considers: 'Authenticity, Appropriateness, and Recomposing the Past', 'Music, Space, and Place: Geography as History', and 'Presentness and the Past: Dialogues between Old and New'. Like the musical collage that is our shared multimedia historical soundscape, it is hoped that this collection is, in its eclecticism, more than the sum of its parts